Pain pressure threshold algometry in knee osteoarthritis: intra- and inter-rater reliability. - Stausholm, Martin Bjørn; Bjordal, Jan Magnus; Moe-Nilssen, Rolf; Naterstad, Ingvill Fjell (Physiotherapy Theory & Practice, 2023)
Synovitis and effusion can cause pain sensitization in persons with knee osteoarthritis (KOA). Pain Pressure Threshold (PPT) algometry is a means to quantify somatosensory abnormalities, including inflammatory-mediated pressure hyperalgesia. We investigated the reliability of PPT algometry with three raters. Twenty-seven persons (50 knees) with KOA, according to the American College of Rheumatology criteria, were included. The PPT of the most tender spot in the joint line of each knee, identified by palpation, was assessed using a digital pressure algometer with a round 1 cm2 rubber tip. The algometer was applied three times with at least twenty-second intervals by three physiotherapists each in a single session. Two of the physiotherapists had no experience with the procedure prior to the study. We estimated the Intraclass Correlation Coefficient (ICC) model 2.1, 95% within-subject standard deviation (sw), and Minimal Detectable Difference (MDD). The mean PPTs ranged from 39.94 to 41.81 Newton (N), the intra-rater ICC ranged from 0.909 to 0.956, the sw ranged from 6.44 to 10.77 N, and the related MDD ranged from 9.11 to 15.23 N. The three raters achieved an inter-rater ICC of 0.707, an sw of 17.68 N, and an MDD of 25.01 N. The results were homoscedastic. Our results indicate that PPT algometry is a suitable method for assessment of pain in osteoarthritic knees. After a short session of PPT procedure training, good intra-rater and acceptable inter-rater ICCs were achieved.